2023
DOI: 10.1021/acs.est.2c05662
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Freshwater Sediments Impact the Role of a Main Bioturbator in Ecosystem Functioning

Abstract: While microplastic transport, fate, and effects have been a focus of studies globally, the consequences of their presence on ecosystem functioning have not received the same attention. With increasing evidence of the accumulation of microplastics at sediment−water interfaces there is a need to assess their impacts on ecosystem engineers, also known as bioturbators, which have direct and indirect effects on ecosystem health. This study investigated the impact of microplastics on the bioturbator Tubifex tubifex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…This alteration in wetting due to freezing could significantly influence the environmental fate of MPs, increasing their mobility and potential ingestion by marine organisms, thus, enter in a food chain. Many studies have demonstrated the toxicity of MPs for benthic fauna, and the MPs in sediment can affect biogeochemical processes by reducing the bioturbation activities of benthic fauna due to their toxic effects. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This alteration in wetting due to freezing could significantly influence the environmental fate of MPs, increasing their mobility and potential ingestion by marine organisms, thus, enter in a food chain. Many studies have demonstrated the toxicity of MPs for benthic fauna, and the MPs in sediment can affect biogeochemical processes by reducing the bioturbation activities of benthic fauna due to their toxic effects. , …”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated the toxicity of MPs for benthic fauna, and the MPs in sediment can affect biogeochemical processes by reducing the bioturbation activities of benthic fauna due to their toxic effects. 31,32 The impact of freezing varies with salinity. While freezing in freshwater affects MP behavior, no significant impact on particle size and stability was observed in saline water compared to control groups in our experiment.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Microplastics in sediments pose a threat to the functioning of ecosystems [21] , particularly as they can be ingested by benthic species and therefore ascend to the food chain and enter human diets [ 22 , 23 ]. For this reason, the development of an effective approach for detecting the distribution and concentrations of microplastics in sediments is indispensable for understanding their availability in aquatic systems and, therefore, the threat presented to aquatic animals and related ecological processes.…”
Section: Additional Informationmentioning
confidence: 99%
“…River sediments are highly variable in their form, necessitating different sampling procedures. They are susceptible to changes in flow and zoogeomorphic processes (Johnson et al, 2020;Wazne et al, 2023) that alter sediment mobility at short (diurnal), long (seasonal), and event-specific (e.g., flooding and drought) time scales (Hurley et al, 2018).…”
Section: Working With Your Environmentmentioning
confidence: 99%